Hydraulic Grade Line and Energy Grade Line Calculations - Bengtson, Harlan (McGraw-Hill's AccessEngineering., 2018)
This Excel workbook will calculate and plot hydraulic grade line and energy grade line for up to 15 points along a storm sewer line, based on user input values for invert elevations, lengths of pipe, pipe diameters, Manning's roughness coefficient, design stormwater flow rates, and surface elevations. The calculations made by the spreadsheet include automated iterative calculation of the normal depth of flow for the partially full pipe flow in each section of storm sewer.